Amygdala fMRI Signal as a Predictor of Reaction Time - Riedel, Philipp; Jacob, Mark J.; Müller, Dirk K.; Vetter, Nora C.; Smolka, Michael N.; Marxen, Michael (Frontiers in Human Neuroscience, 2016)
Reaction times (RT) are a valuable measure for assessing cognitive processes. However, RTs are susceptible to confounds and therefore variable. Exposure to threat, for example, speeds up or slows down responses. Distinct task types to some extent account for differential effects of threat on RTs. But also do inter-individual differences like trait anxiety. In this functional magnetic resonance imaging study, we investigated whether activation within the amygdala, a brain region closely linked to the processing of threat, may also function as a predictor of RTs, similar to trait anxiety scores. After threat conditioning by means of aversive electric shocks, 45 participants performed a choice RT task during alternating 30s blocks in the presence of the threat conditioned stimulus [CS+] or of the safe control stimulus [CS-]. Trait anxiety was assessed with the State-Trait-Anxiety-Inventory and participants were median split into a high- and a low-anxiety subgroup. We tested three hypotheses: 1) RTs will be faster during the exposure to threat compared to the safe condition in individuals with high trait anxiety. 2) The amygdala fMRI signal will be higher in the threat condition compared to the safe condition. 3) Amygdala fMRI signal prior to a RT trial will be correlated with the corresponding RT. We found that, the high-anxious subgroup showed faster responses in the threat condition compared to the safe condition, while the low-anxious subgroup showed no significant difference in RTs in the threat condition compared to the safe condition. Though the fMRI analysis did not reveal an effect of condition on amygdala activity, we found a trial-by-trial correlation between blood-oxygen-level-dependent signal within the right amygdala prior to the CRT task and the subsequent RT. Taken together, the results of this study showed that: Exposure to threat modulates task performance. This modulation is influenced by personality trait. Additionally and most importantly, activation in the amygdala predicts behavior in a simple task that is performed during the exposure to threat. This finding is in line with ‘attentional capture by threat’ - a model that includes the amygdala as a key brain region for the process that causes the response slowing.